Moderating Effect of Independent Directors on the Relationship between Chief Executive Officers Characteristics and Performance of Listed Deposit Money Banks in Nigeria - Yunusa, Ibrahim; Abubakar, Mohammed Babakatun; Umar, Mohammed Maidugu (PT. Riset Press International, 2023)
The study examined the moderating effect of independent directors on the relationship between Chief Executive Officers characteristics and performance of listed deposit money banks in Nigeria. Ex-post facto research design was used and panel data was collected from the audited annual financial statements of thirteen listed DMBs in Nigeria for a period of 2014-2022. Generalized Least Squares (GLS) method of Panel Regression, Fixed and Random Effects was employed in its estimations with the aid of STATA Software Version 14. Performance is dependent variable proxied by Return on Assets and Tobin’s Q, the independent variable is CEO characteristics proxied by CEO tenure, CEO gender, CEO age, CEO educational level, CEO financial expertise, CEO duality, CEO political connection and CEO ownership, the moderating variable is independent directors while board size and bank size are the control variables. The study found that CET, CEG, CEE, CFE, CPC, IDD and CEO have significant positive effect on banks performance, CEA has significant negative effect on banks performance while CED has non-significant positive effect on performance of listed DMBs in Nigeria. Also, the study found that independent directors did not only have a positive and significant direct effect on bank performance, but it also moderates the relationship between CEO characteristics and DMBs performance. However, the study recommends that Central Bank of Nigeria should make it mandatory for DMBs in Nigeria to have a board majorly composed of independent directors since their presence on board strengthens the relationship between CEO characteristics and banks performance.